Katy no-pocket - Payne, Emmy 1919- (Houghton Mifflin, 1944)
Desolate Katy Kangaroo has no pocket in which to carry her son Freddy, so she asks all the other animals how they carry their children and finally goes to the city to find a pocket of her own.